A Variant of the Current Dens Invaginatus Classification - Meisha Gul; Samira Adnan; Fahad Umer (Tehran University of Medical Sciences, 2020)
Endodontic treatment of maxillary incisors may be considered straight forward. However, in some instances, they may exhibit aberrant morphology. One of these rare variations in tooth morphology is dens invaginatus. To improve the endodontic prognosis of such teeth, a detailed evaluation of the tooth under treatment is important, which requires comprehensive clinical and radiographic examinations, including periapical radiography and cone-beam computed tomography (CBCT), which is highly recommended whenever atypical root canal morphology is suspected on a periapical radiograph. The current case report discusses the diagnosis of type IV dens invaginatus in a maxillary lateral incisor using CBCT.